Analysis Of Wind With Battery Connected To Microgrid System - Khamis, Aziah; Mohd Aras, Mohd Shahrieel; Mohd Zambri, Mohd Khairi; Mohd Shah, Hairol Nizam; Ab Rashid, Mohd Zamzuri; Ahmad, Azhar; Jaafar, Azri (IJAERT, 2017)
Nowadays, distributed generation technology had gained more popularity by many countries. Recently, there are many problem with power system. One of the problem is high electricity price. The price in power generation rely largely on the type and market price of the fuel used, government subsidies, government and industry regulation, and even local climate patterns. In order to supply a better power system, this thesis introduces a model of wind turbine and a battery storage connected to microgrid system. The microgrid is the small scale which widely used in power generation system. Microgrid can operate with renewable and nonrenewable energy. Through this project, microgrid will be modelling by using wind turbine and battery storage system.